Intraoperative Management for Left Ventricular Assist Device Implantation With Concurrent Laparoscopic Sleeve Gastrectomy: A Case Series. Issue 11 (5th November 2021) - Kumar, Rishi; Ellis, Sarah; Salas De Armas, Ismael A.; Patel, Manish K.; Akay, Mehmet H.; Bajwa, Kulvinder S.; Liang, Yafen; Gregoric, Igor D.
Abstract : The increasing coincidence of obesity with heart failure may preclude eligibility for orthotopic heart transplantation, requiring continuous-flow left ventricular assist devices (LVADs) as destination therapy. This report describes intraoperative considerations for patients who underwent LVAD implantation with concurrent laparoscopic sleeve gastrectomy (LSG) to promote weight loss. In particular, right ventricular dysfunction associated with acute left ventricular unloading may be compounded by pneumoperitoneum for LSG due to the difficulty in ventilating patients with obesity, hypercarbia-mediated increase in pulmonary vascular resistance, and variable cardiac loading conditions. We identify specific anesthetic challenges and discuss methods of monitoring and management.